Το ημι – προεδρικό σύστημα. Το πολιτικό σύστημα της Γαλλίας (Μέρος 1ο) - ΙΩΑΝΝΗΣ ΠΑΠΑΓΕΩΡΓΙΟΥ (Αριστοτέλειο Πανεπιστήμιο Θεσσαλονίκης, 2022)
: You got you got T your woe need those without those email Corley food they knew he was a you've got ace see me make you've seen let me give you more or less Yes made no money last you got me is the easy Dan not sure got Yeah I mean it's not easy for whole foods this venue to move Yeah you're core is easing a lot of all over the yet those you mom you Vause Yeah E need yet you seem to be it my O of you being with I need your based but guess books came give us you see you this is Healy Yeah Yeah Yeah off the floor Yeah leave owes you a salute evenings using even though that is me up minds is what do you got news kneeing kneeing bloom energy you me we do need you're the huge then I Chung Walsh you need can you give us a needed then you need Yeah it he's very cool of course you better you better not gd enough you've got your get hit not just in the last days Max all of these guys I mean garments blow this off the tee ball for Here's what you need pose for the core of this inside these he mass by talking to the lettuce we rely it saves your we got off easy pieces no floor it's Yeah we need and we won this Yeah there's one here you goals no goal who you see here is I think pass this along a loud Yeah you've got 3 almost let me use this who's got a hard he's using the new there's a young sorry guys I Hi Hey I've made plans Yes so let me be Yeah all Flo Yeah getting BoE you Wow elie Wiesel was all need all got me Lauren Wolfe meeting move Tony Ah nee nee nee Daisy love niche for all what drew me Neil you all I it WA easy Yes even Lou I guess here then the story for us Te' o old one of my being beauty pays for sure Yeah Oh I see heat fire easy home whe Yo I need or these Yeah these days you you you you like we've both seen you use or me movie wall T me me it's all love Nbc's need story of gays RYE Yes he days wall or niche you know Manning's is but we I for Hey who's seen why do you want me us all my own view we go Sea life woo you Yeah my role Apple very believe the eat your whole you I Yeah then he's needs our lady he's your Yeah wait for old this Hugh HUMIRA eat your eases gave then yet your or need for told me me he's ease and ease of use Yeah the all moves I want Oilers these old woes all Yeah picks based my main oil and leave my Blue blood wall one T do you Yeah one of the most Paul Yeah I need missiles we all eat Yes easy this or is that Ole Ole they've all you've just got all United those Blue I eat she time Yeah the us letter through our worries he's smiling all day our goal amazes me he luminous you well you the media these you've got your by saying Yeah wound each he's where he these these Yes TD pass or they love me yet the you we needs all my days Yeah you and for the seat what Yeah I mean this is or see the neediest for Yeah man we Blue be view needs what is Oh Yeah he Lou Yeah Wow Yeah United Mississippi Yeah Yeah Yeah S Li sure will we wall what Yeah what those goals is seen all do not what Wow sprayings all U S he's you want T your honor I must see Yeah Yeah T you school females all need wall halloween all deal for Dec 4 load that is Yeah Yeah Whoa Yeah he goes there was whole lot you Daesh is Yo I need low so Yeah and all of us is eases rules you one fit for us all so you I was me with Willie is this should ease begs to motivate eat food Yeah whole Wow goal for your S you need Magnus me we this is all view you Moos the you more ECB this you always loves these oil use you needs I need your Yeah let me you each one got young Meghan you don't Wash for you match move I'm your need Warner bull he eat excision I will eat this love this guy boy Yeah plus niche you Timor-Leste Yeah Yeah Yeah Yeah I wonder what you eat these ET may gain Yeah we're all Yes Yes Yes Vause you see one of these this mom I see my God if you Lil bow Wow what a mess E Yeah Bowl loss he's the all love you you want all the stuff you see he's got he's let Yes but you see so Yeah you baby you're a human being I see josh flew things but they do believe exit wound stun Wolf he even this is bull bull bull laughing let me see your vehicle that was Yeah get out of here you see that's it for us do these vs may got low the love baby all aleppo I'm bleep one week my who should do it over I don't movie the so Manuel need you studio one I Lazio the Moos I need low well me they love part our nbc leaving me by the way Yeah her role as soon whole this Ghazi all he's Yeah boy or what do you or core when you're I use you the voice core one loss we love Yeah will use road you need Yeah Yeah I me I need you all want for all we've lost these will be dee dee logs we day my House we abo T day Yeah look Whoa you need these hazy we and yet we're live for I us you need for need water niche one lose off wallace Yeah Yeah Yeah and Blues or all these need hot off the use this always be was Yeah police bomb he's man won T Wow Yeah I was all your love we're getting a I game Yeah a use what one wall is me us walk me nice boy always mini me Yeah before you need to use I see your those city hall new York me out Yeah I don't know you flew with us Yeah Yeah while S easy this on PETA's case you've all me one G worth more whole lot alliance for Whoa Whoa he's whether the dvr us Yeah you do not day live whole move off you need is love me you me 0 use Yeah he's O move Meese and these places we need need whose fate is ps more the food we eat more Yes E easy this you wall all need Ruth Yeni me love love is all you your oil off not I lose the yet there's all this man needs is he all you know one of the key role for or year all all he moved you'll see now all we will share move slew you then I'm all I you I fly made seed Yeah Yeah you know these all more me raw or you Yeah loans these niche holed roads and highways this or not Yeah old move was my the East Timor Yeah mine visa all your smile T T goal won the you buy these cells you want I Yeahhhhhh ow ow you have you movie your whole Yeah this is Hue and cry pool knew going up it's just not really only the needs wall when Yeah all balloon popping today you need your mom this you think I the hall wound Lah or maybe O me candidate pool you have grown read the well my base wall Walsh you all mess we're all you Yeah I ink you ow this goal we we this with snow Hayes us wha one was this season v Wu he's v or I will I swear them Bonnie all Yes you Whoa this is not we'll lose these for 5 days Baldwin you want me to see us live pool DC works deal and gays Weir Yes no you won't be Yeah all of us the the us he's got he needs one is this one for the whole time Kaye what blew all of your Yeah smile ands you long get you need to see my Li eat your for one he's the us this year Yeah needed this ishe you race these and you all only with lots of luck Kaye the me United he saw all rules pull my whole easy I mean this is a good now believes Yeah for all those years old you'll the goal Yeah full behd me and not all may owe Moos all of you with us is wall you're the wall Yes sure when all the move me what was this all Yo Yo Ma is we're Stone Yeah what is one whole smile boy you yours in the pain need your with LOL the loss but the we have this lost all your roof those phase right now bottles we know we've got you love the the messages all the time I saw what you need is always going to be for did Yeah me reviews for the you you see we've got you want they all want to be with you my feaess but not me love had hung Yellin all just more we you believe me we're one slated you were we T or were these Yeah he should bear all all smile Yeah we small fire whole Yeah this is were minus Wow no long and need all the for whom you good you see all Daesh led Yeah sees me the main you Moos movies poor me I love please Bowl let one goal all guy Yeah he's got Yeah we these that's your all let us you see Whoa Whoa view fast O you need or Jeanne Moos weighs the for I all these love we only and let v what you we all you want meet me this the bar got the will cede and us we hope you goal the your raw this draw need there's goal Rishi you need was ou you cold this the $ easily or solo Müller leads off our unity these ruling only we'd be even when she was we all want loose ball once you for but this you rare T for me fee niece France we've seen friends Don you know this is Guam all eat yet blew off his owe cruz needs this is game well Yeah all the the you want all you these easy you owe me neither is Baba Boo all the this you unity wall my we don't Wayne you and while all the you these I sd these everyone now you'll eating all of unit you love for seed seeing believe you the this little Yeah movie let I will you love me sure pull you're all the eat one of these wounds and always nice East all you need $ this by way for Yo seen me Seashore the should we you raise you wound wound U S Yes I for me these shows all all around the World for I always Yeah all day long all I you ow you is T ou this Goma Yeah v Yeah anyone us smile goal that's or more your one going era niche brands you Whoa my gosh this all if you a pays for all we're Yes for all seed all need or peen era this all Yeah unity we get for all Yes day loves the Yeah all T the whole need our our view lush amazes me nice for me now love Whoa Whoa bar we need easy ou well you know love wall Whoa or gave days for Manish Mehta we you only needs is Wow we saw mom only me and my phone woman belief phone for we on their own you know mass where you these loss but I go man Moos we each dish needs you've seen a each then I for us Yeah Hey the Yeah me he got using what our vision poppy Hey Hey there's a easy one me you a along his last your this man Yeah roles T blow all of these Daesh Yeah well this is will goal Yeah what is met and seema all you buy what I there won't be a steady stream you already he's got his team for all we